UPAYA MENINGKATKAN KEAKTIFAN BELAJAR PESERTA DIDIK DENGAN PENERAPAN MEDIA PEMBELAJARAN “PASTIK” (PAPAN STIK AKTIF) MATERI BUMI BERUBAH (IPAS) DI KELAS V - yustika afritania; Herdi Ramon; Dinda Yarshal; Wardini (LPPM Universitas Cipta Mandiri, 2025)
This research is motivated by the low level of student engagement in Class V at UPT SDN SPF 101789, particularly in terms of discussions, answering questions, and expressing opinions. The objective of this study was to improve student engagement through the use of the PASTIK (Active Stik Board) learning media on the topic Earth Changes in the IPAS subject. This study employed a Classroom Action Research (CAR) method following the Kemmis and McTaggart design, conducted in two cycles, each consisting of four stages: planning, action, observation, and reflection. The results showed that the implementation of the PASTIK media significantly enhanced student engagement. Initially, only 37% of students were actively engaged in general; after Cycle 1, this rose to 57%, and in Cycle 2, it reached 80%. This significant improvement was observed across all aspects of engagement: discussion, answering questions, and expressing opinions. The use of PASTIK proved effective in creating a more inclusive and participatory classroom atmosphere, encouraging students to interact more confidently during learning.